Moderating Impact of Strategic Vision To The Relationship of Strategic Involvement With Environmental Uncertainty, Competitive Strength, Job Involvement, and Organizational Commitment - Fauzi, Agus (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This research aims to understand the moderating impact of strategic vision to the relationship of strategic involvement with environment uncertainty, competitive strength, job involvement, and organizational commitment. The sample of this research are 72 officials of Muhammadiyah universities in Indonesia which are called Rector, Chief, Director, Vice of Rector, Vice of Chief, Vice of Director, and Dean. This research use survey method with questionnaire as research instrument and nonprobability sampling method, specifically purposive sampling in particular. To test the validity we use confirmatory factor analysis and to test reliability we use coefficient of cronbachâ€™s alpha. To test the hypotheses we use moderated regression analysis. The result of this research shows that strategic involvement is positively related and significant to environment uncertainty, competitive strength, job involvement, and organizational commitment. Strategic vision does not moderate the relationship of strategic involvement with environment uncertainty, but it moderates the relationship of strategic involvement with competitive strength, job involvement, and organizational commitment.Â